Pegylated Gold Nanoparticle (Peg Aunp) Development For Enhancement Of Red Cell Antibody Agglutination Reaction - Cheong, Theng Ho (2019)
Enhancing potentiators such as Low Ionic Strength Solution (LISS) and Polyethylene Glycol (PEG) have been widely used to facilitate red blood cell (RBC) antibody agglutination reaction. Gold nanoparticles with its inert and tunable property, have been proven in fastening this reaction. Hence, this study aimed to develop an alternative enhancing potentiator for RBC antibody agglutination by using the combination of PEG and gold nanoparticle (PEG AuNP).